The Impact of a Walnut-Rich Breakfast on Cognitive Performance Throughout the Day in Healthy Young Adults. (7th June 2021) - Bell, Lynne; Dodd, Georgina; Whyte, Adrian; Shukitt-Hale, Barbara; Williams, Claire
Abstract: Objectives: A healthy diet is essential for optimal brain health. A number of food bioactives have been linked to cognitive benefits, including phytonutrients and essential fatty acids. Here we investigated the benefits of a walnut-rich breakfast, which contained flavonoids and omega-3s,  to see whether consumption of these bioactives might lead to significant cognitive improvements throughout the day. Methods: A double-blind, crossover intervention study compared the effects of a breakfast containing 50g walnuts, with a nut-free, macronutrient-matched control. Participants were 32 healthy, young adults aged 18 to 30. Cognition, mood, blood, and EEG measures were recorded at baseline and 2, 4, and 6 hours postprandially. Only the cognitive data are reported here. All cognitive data were analyzed using linear mixed modeling (LMM) with baseline performance included as a covariate. Bonferroni corrected pairwise comparisons were used to investigate significant treatment effects. Results: Compared to the control breakfast, the walnuts elicited significantly faster reaction times throughout the day on tasks measuring inhibition and task switching aspects of executive function. Memory recall results were mixed; slightly worse performance was observed at 2 hours following the walnut breakfast, but this was later reversed with walnuts outperforming control at 6 hours. Conclusions: The findings provide evidence for reaction time benefits following a walnut-rich breakfast, with effects lasting throughout the day. The results concur with previous literature that suggests executive function effects are commonly observed in young adults following flavonoid supplementation. The memory recall effect at the final time point is consistent with previously observed benefits for both omega-3 fatty acids and flavonoids and may indicate that walnuts offer neuroprotection following long periods of cognitive demand, or that memory benefits depend upon the slower absorption of omega-3s or the delayed appearance of flavonoid metabolites. Walnuts are therefore beneficial to cognitive function in young adults after only a single, acute intake, but further investigation of precise mechanisms is needed. Funding Sources: The study was funded by the California Walnut Commission, USA and pre-registered at clinicaltrials.gov.